COUNSELLING ON ERGONOMIC ASPECTS OF HANDLING METROLOGY STANDARDS AND OCCUPATIONAL SAFETY TOOLS - Annisa Kurnia Citra; Rieska Ernawati; Muhammad Sagaf; Wiwiek Fatmawati; Novi Marlyana (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
A comprehensive study of a community service program focusing on ergonomics and occupational safety at the Regional Technical Service Unit (UPTD) for Legal Metrology in Jepara Regency has been done. The primary focus of this study is to mitigate the risk of musculoskeletal disorders (MSDs) often experienced by metrology officers due to Manual Material Handling (MMH) activities when handling heavy standard test weights (bidur). The background of the program is rooted in the high intensity of physical labor across various consumer environments, such as traditional markets, gas stations, and factories, which frequently overlook basic ergonomic principles. The objective of this program is to educate the implementation team on correct lifting techniques (squat lift), raise awareness of the importance of Personal Protective Equipment (PPE), and evaluate the effectiveness of educational interventions on officer knowledge. The implementation method includes preparation stages, field observation, pre-tests, theoretical material delivery, practical demonstrations, and final evaluation through post-tests and satisfaction questionnaires managed digitally via the Google Forms platform. The results indicate a significant increase in participant understanding by 55.31%, with average knowledge scores rising from 84.67 to 95.4. The discussion explores the relationship between awkward working postures and the potential for occupational accidents, as well as the challenges in building a safety culture within the public sector. The report concludes with the importance of continuous training and the provision of mechanical aids as a long-term solution to maintain the occupational health of metrology officers.